A new association of Oculoauriculovertebral spectrum and persistent fifth aortic arch -double lumen aorta: a case report - İsmail Balaban; Meltem Ceyhan Bilgici; Kemal Baysal (BMC, 2022)
Abstract Background Oculo-auriculo-vertebral spectrum is a heterogeneous group of genetic disorder, also known as Goldenhar Syndrome, which has several phenotypic features including craniofacial anomalies, cardiac, vertebral and central nervous system defects. Cardiovascular anomalies include ventricular septal defects, atrial septal defects, patent ductus arteriosus, Tetralogy of Fallot, double outlet right ventricle, aberrant right subclavian artery, coarctation of aorta, transposition of the great arteries, double inlet left ventricle, cor triatriatum, pulmonary artery stenosis, aortic stenosis, persistent left superior vena cava, partially or totally abnormal pulmonary venous return and bicuspid aortic valve. Persistent fifth aortic arch, also named as double lumen aortic arch, is a very rare cardivascular anomaly and usually associate other cardiac defects. Case presentation We present a 7 month old patient with oculo-auriculo-vertebral spectrum signs as facial asymmetry, short neck, choanal atresia, cleft palate, bilateral preauricular skin tags, bilateral hypoplastic ear lobes, epibulbar dermoid cyst, rib, vertebrae and cardiovascular anomalies. Cardiovascular anomalies detected with echocardiography and computed tomography were malalignment ventricular septal defect and double lumen aorta, known as persistent fifth aortic arch. Conclusion Various cardiovascular anomalies may accompany Goldenhar Syndrome. We present a case with persistent fifth aortic arch and Oculo-auriculo-vertebral spectrum and this is a new association that was not reported before in the literature.